Towards carbon neutrality and water sustainability: an integrated anaerobic fixed-film MBR-reverse osmosis-chlorination process for municipal wastewater reclamation - Wang, Siyu (2022)
Freshwater resilience is facing to an increasing challenge, while carbon neutral wastewater reclamation has been put onto agenda in more and more countries. The activated sludge-microfiltration (MF)-reverse osmosis (RO) process has been currently adopted for reclamation of municipal wastewater to high-grade product water (e.g. NEWater). However, the conventional activated sludge (CAS) unit in this process has the drawbacks of excessive sludge generation, high energy consumption, greenhouse gases (GHGs) emissions etc. To address these emerging issues, an integrated anaerobic fixed-film membrane bioreactor (AnfMBR)-RO-chlorination process was developed in this study. Results showed that about 99.9% of COD, 99.3% of phosphate and 95.3% of NH4+-N were removed in the AnfMBR-RO process, while breakpoint chlorination served as a polishing step when the NH4+-N concentration in RO permeate exceeded the typical NH4+-N concentration (e.g. 1 mg/L) of NEWater. The net energy consumption and total GHG emissions in the proposed integrated process were estimated to be 0.33 kWh/m3 and 310.2 g CO2e/m3 influent wastewater treated, respectively, which were 64% and 74% less than those in the current municipal wastewater reclamation process. Consequently, this study offers an alternative path to bring municipal wastewater reclamation one step closer to carbon neutrality and water sustainability.